Balance sheet expansionary policies in the Euro Area : macroeconomic impacts and a vulnerable versus non-vulnerable comparison : a Bayesian structural VAR approach - Pereira, Francisco Gomes (2023)
Employing a Bayesian structural vector autoregressive (VAR) model, we estimate the impact of the European Central Bank’s (ECB) balance sheet expansionary policies (BSEP) on a range of economic and financial variables including real GDP, inflation, long-term sovereign bond yields, systemic stress, unemployment, bank loans, and equity markets in the period from 2009:Q1 to 2021:Q4. The main conclusion from this study is that more vulnerable euro area countries had larger magnitudes in desirable impulse responses to BSEPs shocks. To reach this conclusion, we estimated the same model for 16 euro area countries and used maximum, minimum, and cumulative impulse responses to assess the heterogenous responses to BSEPs across member states. We then attempt to find correlations of impulse responses with measures of financial and economic vulnerability such as debt-to-GDP ratios, unemployment, GDP per capita (PPP), and tier 1 bank capital ratios. Our results suggest that the magnitude of the responses are more pronounced in countries with higher levels of vulnerability. These findings are akin to theoretical assumptions that suggest that unconventional monetary policies are most effective in periods of severe systemic stress.